PELUANG DAN TANTANGAN EKONOMI KREATIF DI WILAYAH IBU KOTA NUSANTARA (IKN) - Noni, Yovanda (Gapenas Publisher, 2025)
The development of Nusantara Capital City (IKN) as Indonesia’s new administrative center presents strategic opportunities to stimulate the growth of the creative economy sector. This sector serves as a driving force for national economic diversification, focusing on innovation, creativity, and the utilization of local resources. This study aims to identify both the potential and the challenges in developing the creative economy within the IKN area, emphasizing the principles of smart, sustainable, and inclusive development. The research adopts a qualitative descriptive approach through literature review and policy analysis. Findings indicate that subsectors such as architecture, performing arts, interior design, culinary arts, and crafts hold significant prospects, particularly as they align with the rich cultural heritage of East Kalimantan. However, challenges include limited supporting infrastructure, a shortage of skilled creative workers, and the suboptimal harmonization between regulations and the business ecosystem. Therefore, comprehensive cross-sectoral collaboration policies oriented toward community empowerment are required so that the creative economy can serve as the main foundation for economic growth in IKN. This study also recommends that the government and stakeholders position the creative economy as a core element in inclusive and sustainable development planning, prioritizing community participation, social diversity, and the preservation of local culture. Furthermore, the establishment of a responsive and collaborative creative ecosystem is considered strategic to support the sustainable growth of this sector in the IKN area